Pemanfaatan Laboratorium Konseling Sebagai Sumber Belajar Bimbingan Konseling - Manurung, Purbatua (Al-Fikru: Jurnal Ilmiah, 2020)
This study aims to analyze the use of the counseling laboratory as a learning resource for counseling guidance study program students. This study uses a qualitative research method based on library research (library research). Collecting data using documentation techniques derived from library sources. Data analysis uses content analysis techniques where each source or literature used is adjusted and the context is seen for its suitability with other literature from books, journals or other research. In relation to learning resources, the counseling laboratory functions as (1) to provide completeness for the theoretical lessons that have been received so that theory and practice are not two separate things. The two of them are mutually examining and looking for the basis of each other; (2) providing scientific work skills for students/students; (3) provide and cultivate the courage to seek the essence of scientific truth from an object in the natural and social environment; (4) increase skills in using available tools and media to seek and find the truth; (4) fostering student curiosity as a capital for the scientific attitude of a prospective scientist.